The impact of “museum studies” classes that are taught at the fine arts high schools on students ‘attitude - Kavuran, Tamer.; Polat, Bülent (My University, 2016)
High schools that offer art education or vocational training have a direct impact on students' professional lives through the course contents chosen by the students according to their specific interests. Museum studies, that started to gain more importance nowadays, are suggested to help the students strengthen their abilities to make observations, to express their feelings and using their imagination. Moreover, the museum studies can be considered as an education that would certainly affect the students' future life in a positive way. These "museum studies" classes, which are given in the fine arts high schools in Turkey, are included in the curriculum in order to increase the academic and professional background of the art education students. It is very important to find out the problems encountered in "museum studies" classes and come up with solutions. Therefore, the investigation of the curriculum of the "museum studies" course, the way of teaching and whether the desired level of efficiency is reached is of great significance. For this purpose, a survey was applied to the students of the Kaya Karakaya Fine Arts High School who are taking the "museum studies" class, in order to evaluate the change in students' perspective on the concept of "museum" as well as to explain how it contributes to the students' artistic and professional attitudes with concrete examples. According to the findings obtained from the survey results possible solutions were presented.
Bildiri - Yayımlanmış
Keywords: fine arts high school; museum; Art; civilization